Perilaku Kawin Tikus (Rattus norvegicus) Jantan Diabetes Yang Diberi Ekstrak Etanol Kulit Buah Jengkol (Archidendron pauciflorum) - Desak Made Malini; Emay Maulani; Sri Wulandari; Nining Ratningsih (Prodi Magister Ilmu Biologi, Fakultas MIPA, Universitas Udayana, 2020)
Diabetes mellitus (DM) may lead to disruption of normal sexual function in males including abnormalities of orgasmic/ejaculatory function and desire/libido. Simplisia of dried Jengkol fruit peel has been used by people to treat diabetes. The aim of this study was to examine the effectiveness of ethanol extract of jengkol fruit peel (A. pauciflorum) (EEJFP) in improving the sexual behavior of male rats (R. norvegicus) diabetic models. Induction of diabetes was carried out intravenously by using streptozotocin dose 60 mg/ kg BW in the test animals except for the negative control group.The treatments are negative control (Carboxy Methyl Cellulose (CMC) 0.05%), positive control (CMC 0.05%), P1 (EEJFP 385 mg/kg BW), P2 (EEJFP 770 mg/kg BW) and comparison (glibenclamide dose 10 mg/kg BW) for 54 days. The parameters observed are the number of introduction and climbing of male rats to female rats. Data obtained from each parameter were analyzed by analysis of variance (ANAVA) test with a 95% confidence level and Duncan's test. The results of this study indicate that the number of introductions and climbing in the P1 and P2 test animal groups are significantly different from the positive control treatment and close to the value in the negative control treatment group. It can be concluded that the ethanol extract of jengkol fruit peel (A. pauciflorum) affects the sexual behavior of male rats (R. norvegicus) diabetes models by increasing introduction and climbing. Keyword: diabetic, sexual behavior, Archidendron Pauciflorum, rats